(untitled) (Journal of Computational Mathematics, 2018)
In this paper, a class of rectangular finite elements for 2m-th-oder elliptic boundary value problems in n-dimension (m,n≥1) is proposed in a canonical fashion, which includes the (2m-1)-th Hermite interpolation element (n=1), the n-linear finite element (m=1) and the Adini element (m=2). A nonconforming triangular finite element for the plate bending problem, with convergent order O(h^2), is also proposed.